The complete chloroplast genome of Illicium verum and comparative analysis with related species from Magnoliaceae and Illiciaceae - Cao, Yingying; Lai, Yongxing; Li, Zhuxin; Zhai, Shanshan; Dai, Yinghan; Tao, Junyu; Wang, Qing; Xu, Ziheng; Jiang, Minjie; Yu, Li; Leng, Jing; Tang, Haibo (Frontiers in Genetics, 2024)
Illicium verum (Illiciaceae), an ecologically significant endemic plant, predominantly grows in Guangxi, China, which is the primary region for its cultivation. This area accounts for more than 80% of the total cultivation and yield in China. Despite its importance, comprehensive studies on the chloroplast (cp) genome of I. verum are limited. In our research, we sequenced and analyzed the complete cp genome of I. verum and conducted a comparative analysis with nine related species from the families Magnoliaceae, Schisandraceae, and Illiciaceae. The cp genome of I. verum spans 143,187 base pairs (bp), comprising a large single copy (LSC) region of 100,868 bp, a small single copy (SSC) region of 20,235 bp, and two inverted repeats (IR) regions, each 11,042 bp in length. We identified 81 simple sequence repeats (SSRs) within this genome. The chloroplast genome contains 78 protein-coding genes, 8 ribosomal RNA (rRNA) genes, and 35 transfer RNA (tRNA) genes. Structurally, the IR regions exhibit greater similarity across different genera of Magnoliaceae and Illiciaceae compared to the LSC and SSC regions. Phylogenetic analysis revealed high homology between the cp genome of I. verum and those of Illicium burmanicum, Illicium simonsii, and Illicium anisatum. These findings suggest that the cp genome of I. verum may serve as a valuable genomic resource for elucidating the phylogenetic positions and relationships within the Illiciaceae family. This information will be instrumental for future taxonomic research on Illicium species and for advancing genomic studies of these plants.